DESENVOLVIMENTO E AVALIAÇÃO BIOLÓGICA DE NANOPARTÍCULAS DE SORO ALBUMINA BOVINA CONTENDO CURCUMINA - CAMARGO, LUCIANA ERZINGER ALVES DE (2017)
Cancer represents the second cause of non traumatic diseases that can causes death worldwide. There are a wide therapeutic arsenal available and it is composed for sinthetics and natural compounds, however due to their high tocixity and the lack of seletivity, the pacient adhesion is impaired. Curcumin has important biological activities, as well as pronouced effects over several molecular targets, which are involved in the tumor promotion and maintenance. However, curcumin applicability is limited, due to its physicochemical features, such as low aqueous solubility and permeability, chemical instability, resulting in pharmacokinetic drawbacks. The development of nanostructured systems is one of the main strategies to increase curcumin therapeutics efficience. In present work, it was obtained bovine serum albumin nanoparticles containing curcumin, by the desolvation method, and particles shoed spherical morfhology, mean diameter 150 ± 8nm , polydispersity index 0.16 ± 0.02 and zeta potential -32 ± 3mV. The encapsulation efficiency was analysed by high performance liquid chromatography, presentig 45 ± 11%. The physicochemical characterization assay demonstrated the nanoencapsulation process has provided to curcumin amorphous characteristics and interaction between curcumin and the polymer. The stability trial showed the curcumin nanoparticles mantained constant the mean diamether and polydispersity index for 45 days at room or refrigerate temperatures. The curcumin release was prolonged, biphasic and diffusion-dependent. The antioxidant assay, which was performed temporally over the ABTS radical, showed maintenance of the curcumin activity by the nanoparticles for the analyzed period, while the non encapsuled curcumin, showed effect any after 4 hours. The cytotoxicity over normal cells (erythrocytes), it was observed that encapsuled curcumin exerted lower hemolysis significantly than curcumin, while the cytotoxicity over tumor lines (HeLa cell and B16F10) was similar. At in vivo anti tumor activity, performed in melanoma murine model, curcumin loaded nanoparticles showed higher efficiency than curcumin, assessed by the survival and tumor volume in mice. Albumin nanoparticles are efficient curcumin carriers, for its possible biological application, specially, over tumor models analyzed.